Monitoring and managing plant diversity in field margins in Southern England - Havranek, C (2019)
Biodiversity is severely threatened by human activity, with one of the greatest threats coming from agriculture. To reduce the impacts of agriculture on biodiversity, one conservation strategy is to exclude strips of land with herbaceous vegetation from production, termed field margins. Conserving field margins provides a valuable habitat for plant and animal species, and is therefore predicted to boost biodiversity. However, despite being a widely implemented conservation strategy, regular monitoring of plant diversity in field margins is lacking, and the ecological impacts of field margin management are not well understood. This thesis aims to further our understanding of ecologically effective ways to monitor and manage field margin plant diversity, based on three years of fieldwork across four farms in Oxfordshire, England. Based on this fieldwork, four main findings are presented. Firstly, I found that over two years of surveying only a limited amount of variation in plant community composition can be explained by margin-level characteristics. This suggests that margin-level management can only have a limited impact. Secondly, I observed little spatial variation in plant communities between different farms in the same county. This suggests that management recommendations for plant diversity in field margins can be generalised across farms within a region. Thirdly, I observed higher butterfly species richness in field margins with higher plant species richness and intermediate vegetation height. This suggests that management of plant height and diversity will have a positive effect on butterfly diversity. Finally, I found that assessing plant diversity using either transect or quadrat survey methods resulted in biases in the plant species recorded. This suggests that plant surveys in field margins should use both transects and quadrats, to reduce bias in plant species lists. Together, these findings provide ecological evidence to improve conservation efforts for farmland biodiversity, through monitoring and management of field margins.